Corporate market responsibility for orderly financial markets: systemic risk and regulation following Citigroup, sovereign funds, and the credit crunch - Gomes, Rafael A.R. Pereira (2011)
How are companies responsible for helping to ensure orderly financial markets? In economic theory, the question is redundant, because orderly markets result from normal business activity, with support from regulators. Within the last few years, however, several episodes have suggested differently. Citigroup investment bank was fined for destabilising bond markets, despite being absolved of criminal conduct. Sovereign wealth funds were compelled to sign a code-of-conduct, to safeguard "free and open markets", despite having brought economic benefits globally. The US and UK governments described the most profitable financial decade in generations as an "age of irresponsibility", after it led to a crisis. These three episodes are the empirical focus of this thesis.